Pituitary magnetic resonance imaging abnormalities in young female patients with hypogonadotropic hypogonadism - Ji-Yeon Kang; Sang Heum Kim; Hounyoung Kim; Hyojin Ki; Mee-Hwa Lee (Korean Society of Obstetrics and Gynecology, 2019)
ObjectiveTo elucidate the association between clinical and laboratory characteristics and pituitary magnetic resonance imaging (MRI) abnormalities in young female patients with hypogonadotropic hypogonadism (HH).MethodsWe retrospectively investigated a series of 74 female patients (age range, 14-42 years) with normoprolactinemic HH who underwent pituitary MRI. Pubertal milestones and hormonal features of patients with small pituitary glands (PGs) and space-occupying lesions were compared with those of patients with normal PGs.ResultsThe overall frequency of abnormal PGs was 35.1%, with space-occupying lesions observed in 8 patients (10.8%), and small PG observed in 18 patients (24.3%). The mean serum gonadotropin level was not different between patients with and without pituitary MRI abnormalities (P>0.05). Space-occupying lesions were not associated with low gonadotropin levels, type of amenorrhea, or presence of secondary sex characteristics. The frequency of space-occupying lesions was higher in patients with interrupted puberty (25.0%) than in patients who did not go through puberty (4.8%) or had a normal puberty (9.8%), but were not statistically significant (P>0.05). Small PG was associated with low gonadotropin levels and type of amenorrhea (P<0.05).ConclusionClinically significant space-occupying lesions were not associated with low gonadotropin levels, type of amenorrhea, or presence of secondary sex characteristics. However, the frequency of space-occupying lesions was higher in patients with interrupted puberty than in patients who did not go through puberty or who with normal puberty.